The impact of social media on recruitment: Are you LinkedIn? - Tanja Koch; Charlene Gerber; Jeremias J. de Klerk (SA Journal of Human Resource Management, 2018)
Orientation: With many organisations vying for the same talent, it is important to ensure that the correct methods are utilised in identifying and attracting the best talent to an organisation.